FACTORS ASSOCIATED WITH THE UTILIZATION OF ACUPUNCTURE THERAPY AMONG PATIENTS AT THE ACEH PATIENT CARE FOUNDATION (RAPA) ACUPUNCTURE CLINIC, BANDA ACEH CITY - Muhibuddin Muhibuddin; Ayunda Ningtyas K. N; Jubir Jubir (Universitas Bina Bangsa Getsempena, 2026)
Acupuncture is a traditional medicine globally recognized as a complementary therapy for promotive, preventive, curative, and rehabilitative efforts. In Indonesia, including Aceh, this therapy is beginning to be utilized as an alternative or complementary to modern medical treatment. However, utilization rates vary due to the influence of knowledge, health facilities, and the therapist's professional, friendly, and empathetic attitude, which significantly influence patients' decisions to utilize services. Although interest in acupuncture in Aceh is increasing, utilization rates remain relatively low. The purpose of this study was to identify factors associated with acupuncture therapy utilization by patients at the Aceh Patient Care Foundation Acupuncture Clinic in Banda Aceh City in 2025, based on knowledge, health facilities, and the attitudes/behaviors of the acupuncturists. Methods: This study was an analytical survey with a cross-sectional design. The sample size for this study was 99 individuals using the convenience sampling technique. Data analysis was performed using univariate and bivariate methods using the chi-square test. Results: The study showed that there was a relationship between knowledge and the use of acupuncture therapy with a p-value of 0.002 (p<0.05). There was a relationship between health facilities and the use of acupuncture therapy with a p-value of 0.006 (p<0.05). There was a relationship between the attitude/behavior of acupuncture therapists and the use of acupuncture therapy with a p-value of 0.002 (p<0.05). Conclusion: There was a relationship between knowledge, health facilities and the attitude/behavior of acupuncture therapists and the use of acupuncture therapy.